2022
DOI: 10.1007/s11356-022-23910-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of coal consumption, solar, and wind power generation on ecological footprint: evidence from India using Fourier ADL cointegration test

Abstract: In this study, we aimed to assess whether the intensive investments done for renewable energy sources work for reducing environmental deterioration level in India to reach its sustainable development goals and raise environmental quality. To this end, using data from 1995 to 2018, a novel methodology, the Fourier ADL cointegration test, and Bounds test were employed to empirically analyze the long-term steady-state relationship between ecological footprint and renewable and nonrenewable energy sources. Our emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Adedoyin et al (2021) conducted the generalized methods of the moment (GMM) technique, and their empirical findings showed that fossil energy deteriorates the ecosystem in 32 Sub‐Saharan African nations. Karlilar and Emir (2022) conducted Fourier ADL and FMOLS methods to investigate the nexus between solar power and its ecological footprint. Their findings illustrate that solar and wind energy are significantly and harmfully connected to the ecological footprint, considerably reducing environmental deterioration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adedoyin et al (2021) conducted the generalized methods of the moment (GMM) technique, and their empirical findings showed that fossil energy deteriorates the ecosystem in 32 Sub‐Saharan African nations. Karlilar and Emir (2022) conducted Fourier ADL and FMOLS methods to investigate the nexus between solar power and its ecological footprint. Their findings illustrate that solar and wind energy are significantly and harmfully connected to the ecological footprint, considerably reducing environmental deterioration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They discovered that coal transportation and rents both considerably and favorably contribute to the shortand long-term decline of ecological footprints at various quantile ranges. Karlilar and Emir (2023) examine the relationship between fuel usage, renewable energy sources, and ecological impact in India using data from 1995 to 2018. The findings revealed that utilising coal contributes significantly to ecosystem degradation.…”
Section: Non-renewable Energy Consumption and Eiwbmentioning
confidence: 99%
“…Wang et al (2022) reveal the inhibiting effect of FOS on the growth of carbon productivity in 114 countries. Karlilar and Emir (2023) show that the utilization of coal is harmful to the environment in India. Kartal et al (2023) report that the consumption of petroleum, natural gas, and coal harms the ecosystem in France.…”
Section: Literature Reviewmentioning
confidence: 99%